Applications of Istehsān in marital matters In the contemporary context - Minhaj ullah; Prof. Dr. Muhiyuddin Hashmi (jihat-ul-islam, 2021)
The family is the basic institution of the society. If the family is prosperous then the society will be prosperous and if the family is in turmoil then there will be lack of peace and tranquility in the society. The development of science and civilization has affected human life, manners, and marital affairs, as well as other areas of human life, which has led to a number of complex issues, in which following the general rules of Shariah is causing trouble and hardship. istihsan is to abandon the general rules and follow a particular argument. This definition of istishan makes it clear that istishān is one of the means to change the fatwa. istihsan is an important principle by the application of which, according to the circumstances, such orders can be deduced which are based on ease as well as in accordance with the spirit of the shariah. This article provides solutions to marital problems by applying istihsan to contemporary issues.